THE ANXIETY OF AMERICAN MIDDLE CLASS IN PLAY SCRIPT THE HUMANS (2015) BY STEPHEN KARAM - Novrianti Sri Padilla; Leni Marlina (Universitas Negeri Padang, 2019)
This thesis is the analysis of a play script written by Stephan Karam entitled The Humans (2015). It explores the issue of the Anxiety of American Middle Class reflected by the protagonist Erick Blake as an representation of American middle class. It is also intended to find out the contribution of fictional devices such as character, stage direction and setting in revealing the issue of the Anxiety of American middle class. This analysis is related to the concept of Anxiety which developed by Sigmund Freud (1949) that is supported by the text –based and context-based interpretation. The result of the analysis from the play script The Humans (2015) shows about the anxiety of American middle class that experienced by protagonist can be seen through causes and symptoms of anxiety.